Maternally Inherited Essential Hypertension May Be Associated with the Mutations in Mitochondrial tRNAGlu Gene - Wang C; Deng X; Li L; Li M (Dove Medical Press, 2024)
Chun Wang,1 Xin Deng,1 Lei Li,2 Mei Li3 1Department of Integrated TCM & Western Medicine, Mengcheng County Second People's Hospital, Anhui, 233500, People's Republic of China; 2Department of Cardiology, Mengcheng County Second People's Hospital, Anhui, 233500, People's Republic of China; 3Department of Pharmacy, Mengcheng County Second People's Hospital, Anhui, 233500, People's Republic of ChinaCorrespondence: Chun Wang, Department of Integrated TCM & Western Medicine, Mengcheng County Second People's Hospital, Anhui, 233500, People's Republic of China, Tel +86-0558-7623307, Email chunwang0424@163.comBackground: Mitochondrial DNA (mtDNA) mutations are associated with essential hypertension (EH), but the molecular mechanism remains largely unknown.Objective: The aim of this study is to explore the association between mtDNA mutations and EH.Methods: Two maternally inherited families with EH are underwent clinical, genetic and biochemical assessments. mtDNA mutations are screened by PCR-Sanger sequencing and phylogenetic, and bioinformatics analyses are performed to evaluate the pathogenicity of mtDNA mutations. We also generate cytoplasmic hybrid (cybrid) cell lines to analysis mitochondrial functions.Results: Matrilineal relatives exhibit variable degree of clinical phenotypes. Molecular analysis reveals the presence of m.A14693G and m.A14696G mutations in two pedigrees. Notably, the m.A14693G mutation occurs at position 54 in the TψC loop of tRNAGlu, a position which is critical for post-transcriptionally modification of tRNAGlu. While the m.A14696G mutation creates a novel base-pairing (51C-64G). Bioinformatic analysis shows that these mutations alter tRNAGlu secondary structure. Additionally, patients with tRNAGlu mutations exhibit markedly decreased in mtDNA copy number, mitochondrial membrane potential (MMP) and ATP, whereas the levels of reactive oxygen species (ROS) increase significantly.Conclusion: The m.A14696G and m.A14693G mutations lead to failure in tRNAGlu metabolism and cause mitochondrial dysfunction that is responsible for EH.Keywords: EH, mt-tRNAGlu m.A14693G m.A14696G, mitochondrial dysfunction, Chinese families